Produção monitorada on-line por FT-NIR de biodiesel etílico e metílico via catálise homogênea ácida induzida por micro-ondas - Barros, Ewerton Ferreira (2013)
The need for a type of renewable energy and with minimal environmental impact motivates the search for new energy sources and means of producing biofuels. Given this problem, optimized it a Pilot Microwave Reactor (PMR) batch-type all in 304 stainless steel with a nominal capacity of 100 L. To carry out the experiments used anhydrous ethanol and methanol, soybean oil, acidic chesnut oil and sulfuric acid as catalyst, assisted by microwaves. We sought to evaluate the percentage conversion of oil into monoalkyl esters according to the alcohol used and varying the pressure used and the proportion of catalyst in relation to the total volume of reagents and molar ratio oil/alcohol. Among the most important factors that explain the improved performance of the reaction with ethanol is the reaction temperature, because ethanol has a higher boiling point, and the temperature may reach 92 ° C at the end of reaction at ambient pressure, this causes the reaction kinetics is favored. On the other hand, the same is not true with methanol, disadvantaging the forward direction of the reaction even with a larger excess of alcohol. Calibration methods via FT-NIR were constructed by PLS. The first was carried out with the Soy Biodiesel Methyl (BMS) and the second with Ethyl Biodiesel Chestnut (BEC). The same area of the spectra was chosen to do the PLS.